2011
DOI: 10.3945/ajcn.110.004044
|View full text |Cite
|
Sign up to set email alerts
|

Habitual coffee consumption and risk of hypertension: a systematic review and meta-analysis of prospective observational studies

Abstract: The results suggest that habitual coffee consumption of >3 cups/d was not associated with an increased risk of hypertension compared with <1 cup/d; however, a slightly elevated risk appeared to be associated with light-to-moderate consumption of 1 to 3 cups/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 36 publications
4
87
2
20
Order By: Relevance
“…Milk consumption may also serve as a replacement for a sweetened beverage, which was shown to be adversely associated with hypertension risk (13,29). Epidemiological evidence has shown that light-to-moderate coffee consumption may elevate hypertension risk (30), whereas drinking green tea may have a favorable effect on blood pressure (31). We also showed that the inverse association between milk and hypertension was not confounded by intake of these other beverages in this population.…”
Section: Discussionmentioning
confidence: 50%
“…Milk consumption may also serve as a replacement for a sweetened beverage, which was shown to be adversely associated with hypertension risk (13,29). Epidemiological evidence has shown that light-to-moderate coffee consumption may elevate hypertension risk (30), whereas drinking green tea may have a favorable effect on blood pressure (31). We also showed that the inverse association between milk and hypertension was not confounded by intake of these other beverages in this population.…”
Section: Discussionmentioning
confidence: 50%
“…Given that untreated SDB 27 and caffeine intake 28,29 have been linked with hypertension, the absence of prior literature assessing caffeine use in SDB is surprising. While the current study delves into this largely unexplored topic and offers novel fi ndings, equally importantly, it underscores the complexity of delineating caffeine use and highlights areas of future research.…”
Section: Role Of Sponsorsmentioning
confidence: 99%
“…In fact, almost all epidemiologic studies and intervention trials have demonstrated that the consumption of regular roasted coffee does not reduce blood pressure, [22][23][24][25] even though the CGA content in roasted coffee falls within the range which produced anti-hypertensive effects in the previously mentioned studies.…”
Section: Different Roles Of Coffee Components In Blood-pressure Regulmentioning
confidence: 99%